Herbal Teat Care: Effects on Bacterial Count and Teat Condition - Deepthi, V; Malathi, V; Dodamani, Pramod; Kadegowda, Anil K G; Madhura , Y; Suresh , B N; Jolapure, Abhishek Mahadev (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
This study aimed to evaluate the efficacy of diverse herbal teat dipping agents on milk pH and bacterial counts (Staphylococcus, Streptococcus and E. coli), alongside teat condition scoring in 28 days involving 25 lactating Holstein Friesian crossbred cows aged 6 to 8 years. The cows were housed in a loose housing system and categorized into five groups: T1 (Control - water), T2 (1% potassium iodide), T3 (Aloe vera gel), T4 (turmeric paste) and T5 (neem oil), each comprising five cows. The cows’ milk pH, initially averaging 6.46, remained within the acceptable range (6.5-6.7) post-dipping with herbal agents. Aloe vera treatment showed the most significant pH improvement. Bacterial counts did not significantly differ on day 7. Still, by day 28, Staphylococcus counts were significantly lower in neem oil-dipped cows and E. coli counts were lower in all treated groups compared to the control. Teat condition scoring indicated that Aloe vera and potassium iodide positively affected teat skin condition, while neem oil and turmeric paste improved it without significant differences. Teat orifice condition scores remained consistent across groups. The study suggests these herbal agents can be safely used as teat dips without adversely affecting milk pH or teat condition. The findings contribute to understanding the potential of natural substances for maintaining udder health in dairy cows.